Melting temperatures of MgO under high pressure by micro-texture analysis - T. Kimura (Nature Portfolio, 2017)
Melting behaviour of MgO under pressure remains unclear despite the importance of constraining the rheology and composition of the Earth’s mantle. Here, the authors show that melting temperatures in earlier static experiments were underestimated based on micro-texture analysis of the quenched samples.